Communication System Between Charging Station And Electrical Vehicle Using Power Line Communication - Satria Yogsakti, Don Bosko; Purnama, Irwan; Rusdinar, Angga (eProceedings of Engineering, 2025)
Abstract - Electric vehicles are now starting to enter into a regular life, at least in its original sense of the word (for developing countries like Indonesia). In an electric vehicle, there is a little something called the Controlled Area Network (CAN) that serves as the central repository of how different parts in your car communicate with one another like sensors and part conditions. An electric vehicle always comes with a certain amount of charging, which is one of the very essential aspects of running properly. This would be advantageous if the vehicle had a means of communicating with the charging station to provide direct diagnostics on the vehicle's state while it is being charged by simply keeping up its routine maintenance. This is the major reason for the development of Electric Vehicle Power Line Communication (EVPLC). What is intended thereby, is to assure that a data transfer activity with a bidirectional communication mechanism can take place via the AC flowing over via the charging cable of the battery electric vehicle. Realizing the concept, researchers established an EVPLC module with emulated EVCS and EVCAN simulators through online simulation to show it can be deployed into a real electric vehicle (EV) charging station and car. Keywords - CAN, Bidirectional, EVCS, EVCAN, AC